Effect of Music Therapy and Distraction Cards on Anxiety among Hospitalized Children with Chronic Diseases - Soheila Karbandi; Atefeh Soltanifar; Maryam Salari; Seyed Mohsen Asgharinekah; Elahe Izie (Mashhad University of Medical Sciences, 2020)
Background: Hospitalization is recognized as a frightening and stressful experience for children. These negative consequences are intensified when children experience a frequent number of hospitalizations. In this regard, various non-pharmacological approaches have been introduced to reduce these negative consequences, one of which is playing and listening to music. Aim: The present study aimed to determine the effect of music therapy and distraction cards on the anxiety of hospitalized children with chronic diseases. Method: This randomized clinical trial was performed on 83 children with chronic diseases aged 8-12 years who were hospitalized in Akbar Pediatric Hospital in Mashhad, Iran. The participants were assigned to three groups, namely cards, music, and cards + music groups. The intervention which involved listening to favorite music and playing with distraction cards was performed on two consecutive days (duration=20 minutes). Data collection tools included the Spence Children's Anxiety Scale and demographic characteristics questionnaire. Data were analyzed in SPSS software (version 22) using descriptive and inferential statistics. Results: In the current study, the mean scores of children's anxiety in the groups of music, cards, and cards + music after the intervention were reported as 54.8±20.1, 42.7±15.0, and 51.3±15.5, respectively. Moreover, the ANOVA results demonstrated a significant difference in this regard (P=0.038).In addition, the Wilcoxon test results were indicative of a significant difference between the cards (P=0.013) and cards + music (P=0.015) groups regarding the three subscales of anxiety before and after the intervention. Implications for Practice: Playing with distraction cards decreased anxiety and fear in children to a greater extent, as compared to music therapy. Therefore, the active distraction method can be a practical approach to reduce anxiety and fear in hospitalized children.